AIR TEMPERATURE ANALYSIS BASED ON DATA FROM METEOROLOGICAL STATIONS IN THE KASHKADARYA REGION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Global climate change is affecting the water cycle on Earth, further intensifying the uneven distribution of water resources across time and regions. In this regard, the World Meteorological Organization states that "by 2050, nearly 5 billion people will not have adequate access to water for at least one month a year. Overall, global warming is amplifying the Earth's water cycle, with flood-related disasters increasing by 134 percent since 2000, while the number and duration of droughts have increased by 29 percent during the same period." This situation necessitates conducting research aimed at monitoring water resources and utilizing innovative technologies for their optimal management, as well as forecasting river flow.